2015
DOI: 10.1097/imi.0000000000000200
|View full text |Cite
|
Sign up to set email alerts
|

Retained Blood Syndrome after Cardiac Surgery: A New Look at an Old Problem

Abstract: Retained blood occurs when drainage systems fail to adequately evacuate blood during recovery from cardiothoracic surgery. As a result, a spectrum of mechanical and inflammatory complications can ensue in the acute, subacute, and chronic setting. The objectives of this review were to define the clinical syndrome associated with retained blood over the spectrum of recovery and to review existing literature regarding how this may lead to complications and contributes to poor outcomes. To better understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 69 publications
(63 reference statements)
2
32
0
Order By: Relevance
“…We analyzed the need for additional interventions for retained blood defined as any re-exploration for bleeding, delayed sternal closure (DSC), pericardial interventions for drainage (pericardial window or pericardiocentesis), and pleural interventions for drainage for hemothorax or bloody effusions. 8,12 Patients who had the diagnosis of pleural or pericardial effusion or hemothorax but did not undergo a specific invasive intervention or had conservative medical treatment ( i.e. , medications) were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We analyzed the need for additional interventions for retained blood defined as any re-exploration for bleeding, delayed sternal closure (DSC), pericardial interventions for drainage (pericardial window or pericardiocentesis), and pleural interventions for drainage for hemothorax or bloody effusions. 8,12 Patients who had the diagnosis of pleural or pericardial effusion or hemothorax but did not undergo a specific invasive intervention or had conservative medical treatment ( i.e. , medications) were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Chest tubes can become clogged while the patient is still bleeding, leading to retained blood around the heart and lungs. 7,8 Current methods of clearing chest drainage catheters of clot, such as milking, stripping, and open suction are not beneficial, and can be harmful. 8,9 Studies have demonstrated that maintaining chest tube patency with active clearance can reduce the incidence of retained blood, however, protocols of actively maintaining chest tube patency have never been studied in a LVAD population.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the frequent causes of pericardial involvement is the retained blood syndrome (RBS) that develops due to obstruction of chest tubes by clot that initiates vascular endothelial growth factor inflammatory response resulting in increase of tissue exudative permeability and collection of blood in pleura and pericardium. It is observed in about 13.8-22% of patients undergoing surgery and intervention for pericardial effusion and tamponade are required in about 2.7-6.4% of patients (20,21). Its subacute form is associated with development of constrictive pericarditis in 1.2-2.0% of patients (21).…”
Section: Mechanisms Of Pps and Its Complications Development After Camentioning
confidence: 99%
“…It is observed in about 13.8-22% of patients undergoing surgery and intervention for pericardial effusion and tamponade are required in about 2.7-6.4% of patients (20,21). Its subacute form is associated with development of constrictive pericarditis in 1.2-2.0% of patients (21). RBS is defined in presence of 2 of following signs: pleural effusion/ hemothorax requiring drainage, pericardial effusion requiring drainage, reexploration for washout of blood, interventions for postoperative pericardial constriction, interventions for postoperative fibrothorax.…”
Section: Mechanisms Of Pps and Its Complications Development After Camentioning
confidence: 99%